Pengaruh Bentuk Wajah terhadap Pemilihan Frame Ditinjau dari Nilai Estetika di Optik Internasional - Fandi Andrianto; Wahjoe Handini; Adhi Khuntoro (STIKES HAKLI Semarang, 2024)
The high activity levels and various factors that impair a person’s vision have led to an increase in the prevalence of refractive errors. This condition necessitates the use of eyeglass frames to improve visual acuity. However, the development of eyeglass frames today extends beyond merely serving as a tool for visual correction. Eyeglass frames have increasingly become a cosmetic and fashion accessory, as more individuals choose frames based not only on function but also on style. Consequently, many people make incorrect or inappropriate choices when selecting eyeglasses. This has raised questions within the community about whether the shape of a person’s face affects the selection of a frame in terms of aesthetic value. The research method used in this study is quantitative, which analyzes a population in numerical form and presents the findings through statistical analysis. The study was conducted at Optik Internasional Karangploso, located at Jl. Kertanegara No. 15, Malang, with a sample of 30 respondents or consumers. The conclusion drawn from this research is that the choice of eyeglass frame should be aligned with the shape of the face. This not only enhances the visual appearance of the wearer but also boosts their confidence, supporting the overall aesthetic value of the individual.